Episiotomy practices in France: epidemiology and risk factors in non-operative vaginal deliveries - Clesse, C; Cottenet, J; Lighezzolo‑Alnot, J; Goueslard, K; Schefer, M; Sagot, P; Quantin, C (Scientific Reports, 2020)
Episiotomy use has decreased due to the lack of evidence on its protective effects from maternal obstetric anal sphincter injuries. Indications for episiotomy vary considerably and there are a great variety of factors associated with its use. The aim of this article is to describe the episiotomy rate in France between 2013 and 2017 and the factors associated with its use in non-operative vaginal deliveries. In this retrospective population-based cohort study, we included vaginal deliveries performed in French hospitals (N = 584) and for which parity was coded. The variable of interest was the rate of episiotomy, particularly for non-operative vaginal deliveries. Trends in the episiotomy rates were studied using the Cochran-Armitage test. Hierarchical logistic regression was used to identify variables associated with episiotomy according to maternal age and parity. Between 2013 and 2017, French episiotomy rates fell from 21.6 to 14.3% for all vaginal deliveries (p < 0.01), and from 15.5 to 9.3% (p < 0.01) for all non-operative vaginal deliveries. Among non-operative vaginal deliveries, epidural analgesia, non-reassuring fetal heart rate, meconium in the amniotic fluid, shoulder dystocia, and newborn weight (≥ 4,000 g) were risk factors for episiotomy, both for nulliparous and multiparous women. On the contrary, prematurity reduced the risk of its use. For nulliparous women, breech presentation was also a risk factor for episiotomy, and for multiparous women, scarred uterus and multiple pregnancies were risk factors. In France, despite a reduction in episiotomy use over the last few years, the factors associated with episiotomy have not changed and are similar to the literature. This suggests that the decrease in episiotomies in France is an overall tendency which is probably related to improved care strategies that have been relayed by hospital teams and perinatal networks.